2019
DOI: 10.3389/fphar.2018.01470
|View full text |Cite
|
Sign up to set email alerts
|

The Optimal Chinese Herbal Injections for Use With Radiotherapy to Treat Esophageal Cancer: A Systematic Review and Bayesian Network Meta-Analysis

Abstract: Ethnopharmacological relevance: Esophageal cancer is one of the most common human cancers, and its incidence is highly endemic in China. The combination of Chinese herbal injections (CHIs) and radiotherapy should be informed by the best available evidence.Aim of the study: To update and expand on previous work in order to compare and rank the efficacy and safety of CHIs in combination with radiotherapy to treat esophageal cancer.Materials and Methods: We searched several electronic databases to identify random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 57 publications
2
18
0
Order By: Relevance
“…Our early studies also found that combination with CKI can improve the clinical effectiveness rate and performance status of radiotherapy for ESCA. Furthermore, CKI can also provide treatment by reducing gastrointestinal reactions and radiation esophagitis 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Our early studies also found that combination with CKI can improve the clinical effectiveness rate and performance status of radiotherapy for ESCA. Furthermore, CKI can also provide treatment by reducing gastrointestinal reactions and radiation esophagitis 13 .…”
Section: Introductionmentioning
confidence: 99%
“… 11 Due to its ability to reduce the side effects of radiotherapy and increase the survival of cancer patients over a 5-year follow-up period, LNT has been approved as an adjuvant treatment for gastric cancer and colon cancer. 12 - 14 Although the direct antitumor effects of LNT also have been demonstrated in animal models with either primary or implanted tumors, to the best of our knowledge, our data provide the first evidence of the immunotherapeutic potential of LNT in an animal model of bladder cancer. 15 , 16 …”
Section: Discussionmentioning
confidence: 69%
“…After database search, 430 articles were found (PubMed: 34; EMBASE: 30; Web of Science: 28; Cochrane Library: 0; Google Scholar: 338) and 8 meta-analyses met inclusion criteria [9][10][11][12][13][14][15][16]. In particular, three studies were network meta-analyses [9,10,12], whereas the other included research works were standard meta-analyses. The number of clinical studies about lentinan efficacy included in each meta-analysis largely varied, thus ranging from 1 to 65.…”
Section: Resultsmentioning
confidence: 99%
“…Intervention was defined as the administration of lentinan in adjunct to chemotherapy and, in one case, to radiotherapy [9]. Control groups received standard care alone.…”
Section: Resultsmentioning
confidence: 99%